Reimagining the role of teachers in nature-based learning helping children be curious, confident, and caring - Larimore, Rachel; Warden, Claire (New York, NY : Routledge, 2024)
Learn how to integrate nature-based pedagogy in this practical and inviting book. Nature-based teaching is getting more attention in early childhood education settings and can positively impact the development of young children's curiosity, confidence, and care. You'll learn to not only identify but also embody the many roles teachers play when implementing nature-based strategies. Chapters lay out the research and theory behind each role, specific language or behaviors of what that role looks like in practice, and reflexive questions to help educators reflect on their practice. This is perfect for in-service early childhood educators, including infant, toddler, preschool, and elementary providers, interested in more intentional use of nature in their teaching.
Keywords: Science -- Study and teaching (Early childhood); Nature study; Environmental education; Outdoor education; Curiosity in children; Confidence in children; Caring in children; EDUCATION / General